THE PHILANTHROPY OF ISLAMIC BOARDING SCHOOLS IN ECONOMIC EMPOWERMENT - Eko Wahyudi; Subandi; A. Muslimin (Jurnal Dinamika Ekonomi Syariah, 2026)
This study aims to analyze the forms, roles, and impacts of Islamic philanthropy based on pesantren in empowering the community’s economy at Pondok Pesantren Al-Falakhussa’adah. The scope of the research includes philanthropic practices in education, social-humanitarian activities, productive economic programs, and ZISWAF management. This study employs a qualitative method with an empirical approach through field research. Data were collected through observation, semi-structured interviews, and documentation, and analyzed inductively through data reduction, data display, and conclusion drawing. The findings reveal that philanthropic practices in the pesantren have shifted from a charity-based approach toward an empowerment-based model. The programs include scholarships, social assistance, business capital support, and entrepreneurship training. These initiatives have contributed to increasing economic independence, creating new micro-enterprises, improving income levels, and establishing a community-based economic network. In conclusion, Pondok Pesantren Al-Falakhussa’adah has developed an integrative philanthropic model that combines religious, social, and economic values. Although still dominated by consumptive practices, the transition toward productive philanthropy indicates strong potential for sustainable community welfare improvement.